Are Linear and Nonlinear Exchange Rate Exposures Aggravating Agents to Corporate Bankruptcy in Nigeria? New Evidence from the “U” Test Analysis - Rafindadi, Abdulkadir Abdulrashid; Yusof, Zarinah (International Journal of Economics and Financial Issues, 2014)
Several pioneering studies have established that the effect of exchange rate exposure to corporate entities in periods of the financial crisis is no longer linear. To this end, this study explores the position of this argument in a developing country like Nigeria and investigates if the phenomenon could lead to the escalation of corporate survival threats, particularly in crisis and non-crisis periods. In order to ensure this, we analyzed the data of 102 companies consisting of indigenous and multinationals entities’ from 20 sectors of the Nigerian economy from1980-2011. The study employed the ARDL bounds test approach to cointegration and the “U” test methodologies in determining the linear and non-linearity effects of the exposural position of the selected entities’ value. The findings of the study established the existence of non-monotonic relationships between the indigenous entities values and the exchange rate position. The “U” shape relationship was discovered to be the most aggravating agent to these entities survival threats. Surprisingly the relationship between the corporate value of multinational companies in Nigeria and official exchange rate (ERS) is only having a linear relationship. This means that these entities are not heavily exposed to the vagaries of exchange rate changes, meaning they cannot be threatened by bankruptcy in both the crisis and non-crisis periods, which is in contrast to the findings on indigenous entities. As a result of these findings, we recommend to policy makers, the establishment of exchange rate frame-work that is feasible towards enhancing productivity in the real sector corporate entities of the country. Keywords: exposure; linear and non-linear; monotonic and non-monotonic; financial crisis. JEL Classifications: F3; F4; G3